Powder-Based Additive Manufacturing: A Comprehensive Study of Materials, Process Parameters, Equipment, And Economic Efficiency (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The rapid development of powder-based additive manufacturing (AM) has created new opportunities for producing complex metal components with controlled microstructure and high functional performance. Despite the widespread adoption of AM systems, the combined influence of powder characteristics, process parameters, and machine architecture on the final quality of printed parts remains insufficiently clarified. This work presents an integrated experimental and analytical investigation covering material properties, energy–material interaction, equipment capabilities, and the economic feasibility of industrial AM deployment. The results demonstrate that optimized powder preparation combined with energy-efficient parameter windows can significantly reduce microstructural defects and improve mechanical consistency. The findings provide new insights into the integrated optimization of materials, process parameters, and equipment selection, offering a practical decision-making framework for industrial implementation of powder-based AM.